1991
DOI: 10.1203/00006450-199104000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Exogenous Surfactant by Pulmonary Edema Fluid

Abstract: ABSTRACT. Modified natural porcine surfactant was mixed with edema fluid sampled from the airways of hyperoxia-exposed adult rabbits. By varying the concentration of surfactant lipids (10, 25, and 50 mg/mL) and edema fluid proteins (0-280 mg/mL), we obtained a series of preparations with protein to surfactant lipid weight ratios ranging from 0 to 11.2. The surfactant activity of these various mixtures was analyzed with a pulsating bubble (at a lipid concentration of 1 0 mg/mL) or in experiments on immature new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 11 publications
2
40
0
1
Order By: Relevance
“…In addition, both pulmonary edema fluid and fibrinogen have been shown to inactivate pulmonary surfactant (25,49). Edema fluid is leaked into the lung during PCP-related inflammation, and recent studies have demonstrated that fibrinogen is synthesized in the lung during PCP (44).…”
Section: Fig 3 Effect Of Cd8mentioning
confidence: 99%
“…In addition, both pulmonary edema fluid and fibrinogen have been shown to inactivate pulmonary surfactant (25,49). Edema fluid is leaked into the lung during PCP-related inflammation, and recent studies have demonstrated that fibrinogen is synthesized in the lung during PCP (44).…”
Section: Fig 3 Effect Of Cd8mentioning
confidence: 99%
“…However, damage to the surfactant monolayer has already occurred, and a vicious circle is initiated. Protein concentration will rise in the alveolar space and result in a dose-dependent inactivation/inhibition of surfactant (18): surfactant is rate-limiting for the transfer of protein over the alveolar capillary membrane, loss of surfactant function will result in more protein influx, which, in turn, will inactivate/inhibit even more surfactant (17,18,30). Further evidence that the surfactant system is damaged and that no additional fibrosis is present comes from the maximal volume data, which are similar in both groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To study the presence of histological changes in lung morphology, 1 h after instillation of the liposomes, blood was removed from the lungs by perfusion of the pulmonary arteries with warmed saline (37°C) supplemented with 20 IE heparin/ ml. Next, the lungs were fixated as previously described (17). Briefly, after perfusion, the lungs were fixed with a solution consisting of 3.6% formaldehyde and 0.25% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, due to inflammatory injury of the alveolar epithelial surface leading to compromise of the air-fluid barrier, there is leakage of fluid (alveolar oedema) and serum proteins into the airspace. Both alveolar oedema [51] and serum proteins [52] can contribute to surfactant inactivation and dysfunction. Efficacy of exogenous surfactant replacement therapy in acute respiratory failure due to GBS sepsis was studied in a prospective multicentre trial [53].…”
Section: Group B Streptococcus Sepsis In Newborn Infantsmentioning
confidence: 99%